Fluid Pressure Analysis and Process Stability in Sheet Hydroforming with Die For Steel Sheets - Jaber Adil Sh.; Mohammed Adnan I.; Younis Karem M. (Management Systems in Production Engineering)
To increase the process stability and improve the product quality in the sheet hydroforming with die process, it is crucial for identifying and analyzing the dependence of forming pressure on process parameters. The effects of process parameters (blank holder force, frictional condition) on the forming fluid pressure were thoroughly studied experimentally. The main objective is to establish a relationship between the forming fluid pressure and several factors such as blank holder force and friction between die and sheet. The results demonstrate that the maximum fluid pressure increases with increasing blank holder force and friction. Finally, this relationship aims to support calculations and design data and provide control during the SHF-D process.